The Influence of Conflict Management on the Improvement of Educators' Competence, Motivation, and Performance in Islamic Junior High Schools (MTs) in Lembar District - Masjudin, Masjudin; Thohri, Muhammad; Na’amy, Nazar (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to examine the influence of conflict management on the enhancement of educators' competence, motivation, and performance in Islamic junior high schools (MTs) in Lembar District. Utilizing a quantitative approach with a survey method, data were collected through questionnaires from 104 educators across 11 MTs in Lembar District. Data analysis techniques included validity and reliability tests, classical assumption tests, and hypothesis testing through simple and multivariate regression. The results indicate that conflict management significantly influences educators' competence, motivation, and performance. This is evidenced by the Sig. value in the simple regression test for competence at 0.003 (0.003<0.05), for motivation at 0.029 (0.029<0.05), and for performance at 0.001 (0.001<0.05). The theoretical implications of this study highlight the importance of the role of madrasah leadership in managing conflicts within the school environment. Effective leadership in conflict resolution can serve as a basis for leadership theories in the field of education, particularly in the context of Islamic education. These findings also contribute to the development of training programs for madrasah principals, which in turn can enhance educators' competence through the support and guidance provided.